PENERAPAN PASAL 78 UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA - ANSHARULLAH KURNIAWAN ZUFRI (Dinamika, 2023)
AbstractThere are problems in the implementation of the development of Ketapanrame Village, Trawas District, Mojokerto Regency in a democratic manner in accordance with Law Number 6 of 2014 concerning Villages, so a study was conducted to determine the role and constraints of the village government in implementing Article 78 of Law No. 6 of 2014. This research is a research empirical juridical law by using a statutory approach and an analytical approach. The results of the study show that the role of the Village Government, Village Consultative Body (BPD), and Village Owned Enterprises (BUMDes) in carrying out their duties and functions is still not optimal, as stipulated in Article 6 of Law Number 6 of 2014 concerning Villages. There are several factors that become obstacles, namely related to the quality of human resources, the lack of involvement of the Village Consultative Body (BPD) in the preparation of the Government Work Plan (RKP). The government is trying to hold training related to the main tasks and functions of the village government, rearranging regulations related to the Village Consultative Body (BPD) allowances, increasing monitoring and supervision related to village government performance. Keywords: Development, Village Government, SupervisionAbstrakAdanya permasalahan dalam pelaksanaan pembangunan Desa Ketapanrame Kecamatan Trawas Kabupaten Mojokerto secara demokratis yang sesuai dengan Undang-Undang Nomor 6 Tahun 2014 Tentang Desa, sehingga dilakukan penelitian untuk mengetahui peran dan kendala pemerintah desa dalam menerapkan pasal 78 UU No 6 Tahun 2014. Penelitian ini merupakan penelitian hukum yuridis empiris dengan menggunakan pendekatan perUndangUndangan dan pendekatan analitis. Hasil penelitian menunjukan bahwa peran Pemerintah Desa, Badan Permusyawaratan Desa (BPD), dan Badan Usaha Milik Desa (BUMDes) dalam menjalankan tugas dan fungsinya masih belum maksimal, sebagaimana yang sudah diatur dalam Pasal 6 Undang-Undang Nomor 6 Tahun 2014 Tentang Desa. Terdapat beberapa faktor yang menjadi kendala yaitu terkait dengan kualitas sumber daya manusia, minimnya keterlibatan Badan Permusyawaratan Desa (BPD) dalam penyusunan Rencana Kerja Pemerintah (RKP). Pemerintah berupaya mengadakan Pelatihan terkait tugas pokok dan fungsi pemerintah desa, mengatur ulang regulasi terkait tunjangan Badan Permusyawaratan Desa (BPD), meningkatkan monitoring dan pengawasan terkait kinerja pemerintah desa. Kata Kunci: Pembangunan, Pemerintah Desa, Pengawasan.